CIVIL PROCEEDINGS AS A PROCEDURAL FORM OF THE JUDICIAL POWER REALIZATION (Journal of actual problems of jurisprudence, 2020)
The problem of the ratio of legal categories to “civil law” and “civil process” is a debatable one in thecivility procedural doctrine. For the purposes of this study, these legal categories are used as identical.The term “civil proceedings” is used in the current procedural legislation. In the light of the reform of thecurrent procedural legislation, the definition of the concept, purpose and objectives of civil litigation isa relevant. The concept of civil procedure (process) in the doctrine of civil procedural law is debatable.The science of civil procedural law discusses the concepts of a broad and narrow understanding of thecivil process. Proponents of narrow interpretation refer to the civil process only the work of the court toimplement justice in civil cases.As well as the scientific article states theoretical and practical research of civil proceedings as specializationas a procedural form. General provisions having initial importance for such cognition by thescience of civil procedure law are defined and characterized, their influence on specialization and itscharacteristic is also recognized. According to the authors, this approach reflects the development ofbranch domestic legislation and law, legal practice and legal doctrine, with a special role – procedural.It allows to correctly establish and correctly explain, holistically and systematically understand the legalform of the procedural form and its action in accordance with the subject of the judicial examination,when the results achieved are verified, confirmed or denied its perfection.Key words: civil procedure, civil proceedings, arbitration process, procedural form, the science ofcivil procedure law, specialization as a research area.